Hepatic IGF2/H19 Epigenetic Alteration Induced Glucose Intolerance in Gestational Diabetes Mellitus Offspring via FoxO1 Mediation - Jiang, Ying; Zhu, Hong; Chen, Zi; Yu, Yi-Chen; Guo, Xiao-Han; Chen, Yuan; Yang, Meng-Meng; Chen, Bang-Wu; Sagnelli, Matthew; Xu, Dong; Zhao, Bai-Hui; Luo, Qiong (Frontiers in Endocrinology, 2022)
Objective： The offspring of Gestational diabetes mellitus (GDM) has a high predisposition on type 2 diabetes during childhood and adulthood. The aim of the study was to evaluate how GDM exposure contributed to heptic glucose intolerance through a mouse model of diabetes in the latter half of pregnancy. Methods: By creating a GDM mouse model, we tested glucose and insulin tolerance of offspring by intra-peritoneal glucose tolerance test (IPGTT), insulin tolerance test (ITT) and pyruvate tolerance test (PTT). In addition, we checked the expression of genes IGF2/H19, FoxO1, and DNMTs in the mouse liver by RT-qPCR. Pyrosequcing was used to detect the methylation status on IGF2/H19 DMRs. In vitro insulin stimulation experiments were performed to evaluate the effect of different insulin concentrations on HepG2 cells. Moreover, we detect the interaction between FoxO1 and DNMT3A by Chip-qPCR and knock-down experiments on HepG2 cells. Results: We found the first generation of GDM (GDM-F1) exhibited impaired glucose tolerance (IGT) and insulin resistance, and male offspring demonstrated more obvious than females. In addition, the expression of imprinted genes IGF2 and H19 was downregulated in male mice liver, caused by hypermethylation status of IGF2-DMR0, IGF2-DMR1. Furthermore, increased expression of transcriptional factor FoxO1 was confirmed to regulate DNMT3A expression, which contributed to abnormal methylation status of IGF2/H19 DMRs. Besides, different insulin treatment on HepG2 demonstrated those genetic alterations might induced by intra utero hyperinsulinemia environment. Conclusion: Our results demonstrated that intrauterine hyperinsulinemia environment increased hepatic FoxO1 levels, subsequently increased expression of DNMT3A and epigenetic alterations on IGF2/H19 DMRs. These findings provide a potential molecular mechanisms responsible for glucose intolerance and insulin resistance in the first male generation of GDM mice.